Hungarian Monitoring, 11 October 1989 . [Magyar rádiófigyelő], 1989. október 11 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - International reactions to formation of Hungarian Socialist Party (MSZP) - Baker interview on CBS - Poland: introduction of food stamps - Polish United Workers' Party leader in talks in Moscow - Czechoslovak Central Committee criticizes Hungary - Kürt Hager urges reforms in the GDR Domestic Affairs: - Miklós Németh visits Prague - Hungarian Socialist Party (MSZP) founding meeting - Iván Pető on the Hungarian Socialist Party (MSZP) congress - Hungarian Socialist Workers' Party (MSZMP)-Hungarian Socialist Party (MSZP) compromise - Interior Ministry opposition talks - Ófalu radioactive waste burial site - Independent Smallholders', Agrarian Workers and Civic Party (FKGP) international press conference - Alliance of Young Democrats (Fidesz)-Alliance of Free Democrats (SZDSZ) demonstration in National Museum gardens Külpolitika: - Az MSZP megalakulásának nemzetközi visszhangja - Baker interjú a CBS TV-ben - Lengyelország: élelmiszerjegy bevezetése - Moszkvában tárgyal a LEMP vezetője - A csehszlovák KB bírálja Magyarországot - Reformokat sürget az NDK-ban Kurt Hager Belpolitika: - Németh Miklós prágai látogatása - MSZP alakuló ülés - Pető Iván az MSZP kongresszusról - MSZMP-MSZP kompromisszum - BM ellenzék tárgyalások - Ófalui rádióaktív hulladék-temető ügy - FKGP nemzetközi sajtótájékoztató - FIDESZ-SZDSZ tüntetés a Múzeumkertben